A study of the patterns of maintenance and problems of nuclear medicine instrumentation in the Philippines - Puga, Gonzalo S.
In a study conducted by the International Atomic Energy Agency (IAEA) Medical Applications Section, it has been estimated that millions of dollars worth of nuclear medicine instrumentation acquired by developing countries have been non-functional and are, therefore, lost to productive service. This thesis aims to take a more in depth study of the actual situation in the Philippines by analyzing the patters of maintenance and instrumentation problems of three (3) typical laboratories: the Arrmed Forces of the Philippines Medical Center, the Dr. Jose R. Reyes Memorial Hospital, and the Health and Physics Modular Laboratory of the Philippine Atomic Energy Comission.